A clinical measure of suicidal ideation, suicidal behavior, and associated symptoms in bipolar disorder: Psychometric properties of the Concise Health Risk Tracking Self-Report (CHRT-SR). (December 2015) - Ostacher, Michael J.; Nierenberg, Andrew A.; Rabideau, Dustin; Reilly-Harrington, Noreen A.; Sylvia, Louisa G.; Gold, Alexandra K.; Shesler, Leah W.; Ketter, Terence A.; Bowden, Charles L.; Calabrese, Joseph R.; Friedman, Edward S.; Iosifescu, Dan V.; et al.
Abstract: Objective: People with bipolar disorder are at high risk of suicide, but no clinically useful scale has been validated in this population. The aim of this study was to evaluate the psychometric properties in bipolar disorder of the 7- and 12-item versions of the Concise Health Risk Tracking Self-Report (CHRT-SR), a scale measuring suicidal ideation, suicidal behavior, and associated symptoms. Methods: The CHRT was administered to 283 symptomatic outpatients with bipolar I or II disorder who were randomized to receive lithium plus optimized personalized treatment (OPT), or OPT without lithium in a six month longitudinal comparative effectiveness trial. Participants were assessed using structured diagnostic interviews, clinician-rated assessments, and self-report questionnaires. Results: The internal consistency (Cronbach α) was 0.80 for the 7-item CHRT-SR and 0.90 for the 12-item CHRT-SR with a consistent factor structure, and three independent factors (current suicidal thoughts and plans, hopelessness, and perceived lack of social support) for the 7-item version. CHRT-SR scores are correlated with measures of depression, functioning, and quality of life, but not with mania scores. Conclusions: The 7- and 12-item CHRT-SR both had excellent psychometric properties in a sample of symptomatic subjects with bipolar disorder. The scale is highly correlated with depression, functioning, and quality of life, but not with mania. Future research is needed to determine whether the CHRT-SR will be able to predict suicide attempts in clinical practice. Highlights: This is the first study to validate a suicide scale in bipolar disorder. The Concise Health Risk Tracking Self-Report form has good psychometric properties. The 7-item scale appears to be as good as the 12-item scale. CHRT-SR scores are correlated with depression but not with mania scores. The scale may have utility in clinical practice.